2005
DOI: 10.4081/ijas.2005.2s.467
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cured lard of Cinta Senese pig fed acorn and chestnut

Abstract: RIASSUNTO (29,9 vs. 26,4 vs. 19,9), per "untuosità" (35,5 vs. 33,4 vs. 26,1) e per "gradimento complessivo" (44,8 e 44,3 vs. 40,6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
1
1
Order By: Relevance
“…These outcomes do not agree with those shown previously by Cobos et al [ 52 ] and Díaz et al [ 53 ], who observed that the inclusion of chestnuts reduced the TBARS index in pork meat and its derivates. At the same time, our research also do not agree with other studies that did not find any significant difference in lipid oxidation after using chestnuts in pig fattening [ 54 , 55 , 56 , 57 ]. The increase in TBARS value that occurred in our inquiry could be due to the fact that CH samples present a higher percentage of intramuscular fat ( Table 1 ); therefore, it would be normal to present a higher oxidation.…”
Section: Resultscontrasting
confidence: 99%
“…These outcomes do not agree with those shown previously by Cobos et al [ 52 ] and Díaz et al [ 53 ], who observed that the inclusion of chestnuts reduced the TBARS index in pork meat and its derivates. At the same time, our research also do not agree with other studies that did not find any significant difference in lipid oxidation after using chestnuts in pig fattening [ 54 , 55 , 56 , 57 ]. The increase in TBARS value that occurred in our inquiry could be due to the fact that CH samples present a higher percentage of intramuscular fat ( Table 1 ); therefore, it would be normal to present a higher oxidation.…”
Section: Resultscontrasting
confidence: 99%
“…Even though the differences among groups were not significant, an improved oxidative stability of dry-cured hams from the tannin group compared to the control was indicated. In agreement with our study, no influence on the oxidative stability of fresh meat and dry-cured products was reported for pigs fed tannin rich chestnut or acorn despite their high content of pro-oxidant unsaturated fatty acids [54][55][56][57].…”
Section: Discussionsupporting
confidence: 93%
“…A less pronounced effect on color of dry-cured bellies was shown in sweet chestnut wood supplemented pigs, which exhibited a darker muscle and darker and less yellow fat tissue. No differences in objective color parameters of fat tissue were observed in the seasoned fat of chestnut fed Cinta Senese pigs [46], while sensory evaluated pinkness and yellowness of cured lard were lower and higher, respectively, in pigs fed chestnut diets [54,55].…”
Section: Discussionmentioning
confidence: 84%